2002
DOI: 10.1016/s0895-7061(01)02281-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulse pressure and diurnal blood pressure variation: association with micro- and macrovascular complications in type 2 diabetes

Abstract: Increased PP and blunted diurnal BP variation are hemodynamic abnormalities associated with micro- and macrovascular complications in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 30 publications
9
72
1
2
Order By: Relevance
“…It was also recently shown that in patients with reduced renal function, BP remains high for a longer period of time after going to bed compared with patients with normal renal function [20]. Previous investigators have also found that a blunted diurnal BP pattern is associated with the prevalence of nephropathy in patients with type 2 diabetes [21]. In the light of these findings, we find it noteworthy that in our cohort of clinically normotensive patients, nocturnal systolic BP was independently associated with aortic PWV after adjustments for age, sex, BMI, HbA 1c and blood pressure-lowering medication, but that this association did not remain significant after further adjustments for creatinine levels.…”
Section: Discussionmentioning
confidence: 97%
“…It was also recently shown that in patients with reduced renal function, BP remains high for a longer period of time after going to bed compared with patients with normal renal function [20]. Previous investigators have also found that a blunted diurnal BP pattern is associated with the prevalence of nephropathy in patients with type 2 diabetes [21]. In the light of these findings, we find it noteworthy that in our cohort of clinically normotensive patients, nocturnal systolic BP was independently associated with aortic PWV after adjustments for age, sex, BMI, HbA 1c and blood pressure-lowering medication, but that this association did not remain significant after further adjustments for creatinine levels.…”
Section: Discussionmentioning
confidence: 97%
“…Other data from this cohort have previously been reported. 12,17 Patients were followed for a mean of 9.5 (range 0.5-14.5) years until death or until 1 April 2008. Follow-up data were available for 108 patients, as 10 patients were excluded due to incomplete 24-h ABPM measurements (three patients), migration (two patients) or incomplete records on CV outcomes (five patients).…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, only a few BP parameters were evaluated in each of these studies and the potential interaction between BP parameters were not examined. Moreover, some studies report the association with total mortality, not with CV mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In patients with type 2 diabetes with micro-and macrovascular complications PP is higher than in those without complications. 8 It has also been reported that PP is independently associated with cardiovascular mortality in individuals with type 2 diabetes and PP is a better predictor of coronary heart disease (CHD) events than systolic blood pressure (SBP). [9][10][11] The results of the FinnDiane Study showed that early age-related rise in office PP was more pronounced in subjects with diabetic nephropathy, but was also evident in diabetic subjects with normal albumin excretion.…”
Section: Introductionmentioning
confidence: 99%